FCGR3B gene copy number variation and host susceptibility to vascular leakage in Dengue Hemorrhagic Fever / Hoh Boon Peng , Sazaly Abu Bakar and Rafidah Hanim Shueb - Hoh, Boon Peng; Abu Bakar, Sazaly; Hanim Shueb, Rafidah (Research Management Institute (RMI), 2011)
DENV causes significantly more human disease than any other abovirus. Annually, an estimated of 50-100 million cases of severe dengue require hospitalization in which 500,000 resulted in DHF/DSS, with more than 20,000 death worldwide (WHO DengueNet report, 2005). Hence, it has now been recognized as a major expanding public health problem of the country. Dengue viruses cause a spectrum of illness ranging from asymptomatic infection or mild febrile illness to severe and fatal hemorrhagic disease. While majority experience uncomplicated Dengue Fever (DF), Dengue Hemorrhagic Fever (DHF) can present with severe clinical manifestations including transient vascular permeability resulting in plasma leakage (WHO, 1997). No specific treatment is available to date. Previous studies suggested the involvement of the events in the peripheral blood in association with the DENV disease severity, such as dengue viral replication, cytokine expression, and cellular activation / proliferation and robust host inflammatory immune response (Rothman, 2004). Antibody-dependent enhancement of viral replication is the most widely accepted explanation for the association between DHF and pre-existing antibody. However, it remains considerable uncertainty as to how virus-host interaction triggers the inflammatory response resulting in plasma leakage, the hallmark of DHF/DSS. FcGRII has been reported to play a role in pathogenesis of severe dengue infections (Loke et al., 2002; Littaua et al., 1990). It functions to mediate antibody enhancement in vitro by binding to virus-IgG complexes. A fundamental to any discussion of DENV pathogenesis is the association of secondary infection with heterologous serotypes with DHF/DSS. Antibody Dependent Enhancement (ADE) model during secondary infections, postulates that DENV specific antibodies either cross reactive antibodies, can interact with DENV without neutralizing the virus, and thereby requires FcG receptors to mediate entry of antibody coated DENV into cells (Clyde et al., 2006; Coffey et al, 2009). Therefore, this proposed study investigated and to characterized the CNV of FcGRII gene among the DF and DHF patients. Though association of FcGRII gene SNP polymorphism with dengue has been reported earlier (Loke et al, 2002), none investigated the copy number of this gene and its association to the susceptibility of plasma leakage.